Decontamination of Listeria monocytogenes in king oyster mushrooms (Pleurotus eryngii) by combined treatments with organic acids, nisin, and ultrasound. (June 2021) - Yoon, Jae-Hyun; Jeong, Do-Young; Lee, Su-Bin; Choi, Songyi; Jeong, Myeong-In; Lee, Sun-Young; Kim, Se-Ri
Abstract: This study was conducted to evaluate the effectiveness of 1–3% organic acids alone or in combination with 0.1% nisin and/or 40 kHz ultrasound (US) on the reduction of Listeria monocytogenes in king oyster mushrooms stored at 25 °C. While L . monocytogenes in king oyster mushrooms was reduced by 3.01 log CFU g −1 after dipping in 3% malic acid (MA) at 25 °C for 30 min, the application of 40 kHz US and 0.1% nisin resulted in 0.30 and 2.25 log-reductions, respectively. When L . monocytogenes in mushrooms was subjected to a combined treatment with 3% MA, 0.1% nisin, and 40 kHz US at 25 °C for 20–30 min, this bacterium dropped to <1.48 log CFU g −1, leading to a significant collapse in the cytoplasm with formation of intracellular ruptures and breakage of cell membranes. Synergistic effect of MA-nisin dipping incorporated with US was observed in a food model. Highlights: Synergistic effect of 3% MA, 0.1 g 100 mL −1 nisin, and 40 kHz US was observed in a food model. MA and nisin dipping incorporated with US reduced L. monocytogenes in mushrooms by ≥ 5.0 log CFU g −1 . After combined treatments, no changes in the texture of mushrooms were observed.